DISTRIBUTION AND MEDICINAL PROPERTIES OF SOME TYPES OF ROSE HIPS (ROSA) IN THE CITY OF FERGANA (Scientific journal of the Fergana State University, 2024)
It is known that Rosehip (lat. Rosa) is a genus of plants of the Rosaceae family of the Rosales order, and is of great practical importance. In some countries they are widely used as ornamental plants, and some cultivated species are cultivated to obtain valuable essential oil. It should be noted that the fruits of many wild Namatak species contain a high percentage of ascorbic acid and serve as a source of vitamin C.